FEMALE SAINTS AND HOLY PLACES IN BUKHARA - Rajabov O.I (Western European Studies, 2024)
This article analyses the history of formation of such shrines as Kizbibi (Qizbibi) and Hazrat Bibi, located on the territory of Bukhara province, as well as religious views related to it.
Keywords: Historic hill; shrine; place of pilgrimage; Ogoyi Buzruk